HOW EXTRINSIC MOTIVATION AFFECT PERFORMANCE OF JASIJUKA SEJAHTERA MSME ASSOCIATION IN EAST BELITUNG - Hartanto, Chandra; Sumbogo, Ignatius Ario (Universitas Pelita Harapan, 2022)
This study is structured to determine the effect of extrinsic motivation and digital marketing training on performance. This quantitative approach research conducted with the unit of analysis of the Jasijuka Sejahtera MSME Association, with population of 32 people representatives of Jasijuka Sejahtera. The sampling method used is non-probability sampling with saturated sample technique. The data processing uses multiple linear regression analysis. The result concludes that there is an insignificant effect of digital marketing training on performance, while extrinsic motivation has a positive, significant influence on performance. And last, there is no simultaneous effect between digital marketing training and extrinsic motivation on performance.